2023
DOI: 10.1002/jum.16312
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Point‐of‐Care Ultrasound for Acute Scrotal Pain in the Pediatric Emergency Department

Abstract: ObjectivesTesticular torsion (TT) is a pediatric surgical emergency that requires prompt treatment. This study investigated the feasibility of point‐of‐care ultrasound (POCUS) for diagnosing TT in the pediatric emergency department (ED).MethodsWe retrospectively reviewed the medical records of patients, aged 18 years or younger, who visited a university‐affiliated hospital pediatric ED with acute scrotal pain without trauma history and underwent diagnostic ultrasounds between January 2010 and October 2022.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…A subsequent meta-analysis found that POCUS had pooled sensitivity and specificity of 98.4% and 97.2% for testicular torsion [12]. Scrotal POCUS can be performed an average of 38-73 minutes before radiology performed ultrasound [11][12][13], has been shown to decrease PED length of stay by 77 minutes [13], and to decrease time to orchiopexy by over an hour [14].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent meta-analysis found that POCUS had pooled sensitivity and specificity of 98.4% and 97.2% for testicular torsion [12]. Scrotal POCUS can be performed an average of 38-73 minutes before radiology performed ultrasound [11][12][13], has been shown to decrease PED length of stay by 77 minutes [13], and to decrease time to orchiopexy by over an hour [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies have evaluated the implementation of POCUS pathways for acute scrotal pain in the pediatric ED. Park et al [79 ▪ ] performed a retrospective analysis of their POCUS pathway for acute scrotal pain, and found that patients in the POCUS group had a shorter ED length of stay (EDLOS) (93 vs. 170 min, P < 0.001), as well as high test sensitivity and specificity (94.7% and 92.9%). Similarly, Koppel et al [80] retrospectively compared patients who underwent POCUS vs. radiology US (RADUS) for testicular torsion; those in the POCUS group had a shorter time from arrival to orchidopexy (121 vs. 184, P = 0.036), and shorter EDLOS.…”
Section: Clinical Pathways Integrating Point-of-care Ultrasound For E...mentioning
confidence: 99%